Laporan Keuangan UTD PMI Provinsi Sulawesi Tengah: Apakah Sudah Sesuai Dengan ISAK No. 35? - Ratu Subaeda; Syamsul Syamsul; Dini Rosyada (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The preparation of the financial statements of non-profit organizations since 1997 is regulated in the Statement of Financial Accounting Standards (PSAK) No. 45 Concerning Financial Reporting of Non-Profit Organizations. However, starting in 2019, PSAK 45 was replaced with Interpretation of Financial Accounting Standards (ISAK) No. 35 Regarding the Presentation of Financial Statements of Non-profit Oriented Entities. The purpose of this study is to identify and analyze the application of ISAK No. 35 on the preparation of the financial statements of UTD PMI Central Sulawesi Province. This research is a qualitative research with an interpretive approach. The results of the study conclude that the financial statements of UTD PMI Central Sulawesi Province have been compiled based on ISAK No. 35. The financial statements presented by UTD PMI Central Sulawesi Province are in the form of a statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flow and notes to financial statements.